The longitudinal impact of the COVID-19 pandemic on health behaviors, psychosocial factors, and cognitive functioning in older adults - Hausman, Hanna K.; Dai, Yunfeng; O’Shea, Andrew; Dominguez, Vanessa; Fillingim, Matthew; Calfee, Kristin; Carballo, Daniela; Hernandez, Cindy; Perryman, Sean; Kraft, Jessica N.; Evangelista, Nicole D.; Van Etten, Emily J.; et al. (Frontiers in Aging Neuroscience, 2022)
Background: Older adults are at a greater risk for contracting and experiencing severe illness from COVID-19 and may be further affected by pandemic-related precautions (e.g., social distancing and isolation in quarantine). However, the longitudinal impact of the COVID-19 pandemic on older adults is unclear. The current study examines changes in health behaviors, psychosocial factors, and cognitive functioning in a large sample of older adults using a pre-pandemic baseline and longitudinal follow-up throughout 9 months of the COVID-19 pandemic. Methods: One hundred and eighty-nine older adults (ages 65-89) were recruited from a multisite clinical trial to complete additional virtual assessments during the COVID-19 pandemic. Mixed effects models evaluated changes in health behaviors, psychosocial factors, and cognitive functioning during the pandemic compared to a pre-pandemic baseline and over the course of the pandemic (i.e., comparing the first and last COVID-19 timepoints). Results: Compared to their pre-pandemic baseline, during the pandemic, older adults reported worsened sleep quality, perceived physical health and functioning, mental health, slight increases in depression and apathy symptoms, reduced social engagement/perceived social support, but demonstrated better performance on objective cognitive tasks of attention and working memory. Throughout the course of the pandemic, these older adults reported continued worsening of perceived physical health and function, fewer depression symptoms, and they demonstrated improved cognitive performance. It is important to note that changes on self-report mood measures and cognitive performance were relatively small regarding clinical significance. Education largely served as a protective factor, such that greater years of education was generally associated with better outcomes across domains. Conclusions: The present study provides insights into the longitudinal impact of the COVID-19 pandemic on health behaviors, psychosocial factors, and cognitive functioning in a population disproportionately affected by the virus. Replicating this study design in a demographically representative older adult sample is warranted to further inform intervention strategies targeting older adults negatively impacted by the COVID-19 pandemic.